PSIKOEDUKASI TENTANG EKSPRESI EMOSI PADA PELAKU RAWAT LANSIA DENGAN DEPRESI PASCA STROKE - Lintuuran, Rivo Mario Warouw; Rorong, Agnes Tineke Waney; Satyasari, Daniella; Syafita, Arvia; Kogoya, Alvionita; Hartono, Adinda Mozart Rahmadhina Riyandi; Zachrani, Aliviannisa Hasmah; Suyanto, Alysa Naila Putri; Puteri, Amara Alifia; Kusharianto, Andhika Arief (Universitas Trisakti, 2024)
Post-stroke depression may worsen the wellbeing of elderly with stroke. Depression in elderly may be contributed by psychosocial factors including emotional expression in the family or caregiver. Objective: To identify and manage post-stroke depression in elderly and caregiver emotional expression which may impact patient’s physical and mental health. Methods: Data collection was taken at Krendang by means of visiting patient’s home and conducting interview, observation, and physical/mental examination. Results: A 63-year-old woman post stroke one year ago, was found with hypertension and left hemiparesis. Clinical and psychometric evaluations (Geriatric Depression Scale score 8, Abbreviated Mental Test score 7) yielded depression and decline cognitive function. Psychosocial issues revealed high emotional expression and anxiety in caregiver. Psychoeducation on physical and mental condition was provided to patient and family, especially in controlling emotional expression in caregiver. Conclusion: Psychoeducation on emotional expression and its management may help increase patient and caregiver’s quality of life.